Effects of packaging on bone marrow discoloration in beef arm, rib, shoulder blade, and thoracic vertebra bones - Grobbel, J.P.; Dikeman, Michael E.; Smith, J. Scott; Kropf, Donald H.; Milliken, George A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Meat retailers have reported bone marrow discoloration to be a problem, especially in modified-atmosphere packages (MAP). To evaluate causes of bone marrow discoloration in different beef bones and packaging systems, 36 beef arm bones, ribs, shoulder blades, and thoracic vertebrae from USDA Select and Choice carcasses were obtained from a commercial abattoir, cut into 1-inch-thick sections at 4 days postmortem, and packaged into 1) polyvinyl chloride film (PVC) overwrap; 2) high-oxygen (80% O2, 20% CO2) MAP; or 3) ultra-low-oxygen (70% N2, 30% CO2) MAP. Packages were displayed under continuous fluorescent lighting for 4 days at 35.6°F. Ribs, shoulder blades, and thoracic vertebrae packaged in PVC and high-oxygen MAP developed undesirable gray or black discoloration during display. In ultra-low-oxygen MAP, mean visual-color scores were acceptable throughout display. The a* values (larger values equate to redder color) for ribs, shoulder blades, and thoracic vertebrae decreased (P<0.05) over time. Arm-bone marrow had less oxidation and dramatically less total iron and hemoglobin than did marrow from ribs and thoracic vertebrae. The much larger amounts of iron and hemoglobin in ribs and thoracic vertebrae likely correspond to marrow discoloration. In summary, bone marrow discoloration occurs in ribs, shoulder blades, and thoracic vertebrae packaged in PVC or high-oxygen MAP. Bones packaged in ultralow- oxygen MAP or arm bones packaged in PVC or high-oxygen MAP had minimal oxidation and discoloration.
Keywords: Beef; Bone marrow discoloration; Arm; Rib; Shoulder blade; Throacic vertebrate